PERANAN BAHASA INDONESIA DALAM ERA GLOBALISASI - Tri Indah Kusumawati (NIZHAMIYAH, 2018)
Language in globalization era has an important role, Indonesian people is hoping to use Indonesian language as its function. Thought, globalization era include in many aspects such as economy, technology and language. This article discussed about the development of Indonesian language, existence of in globalization ers and others.